Dopaminergic mechanisms underlying the reduction of electrical coupling between horizontal cells of the turtle retina induced by d-amphetamine, bicuculline, and veratridine - Piccolino, M (J Neurosci, 1987)
Previous studies have shown that dopamine, bicuculline, or d- amphetamine reduce the electrical and dye-coupling between the axon terminals of the horizontal cells of the turtle retina (see Piccolino et al., 1984). In the present study we observed similar effects following the application of veratridine. The actions of all these drugs were prevented by dopamine antagonists acting on D1 receptors such as flupenthixol and SCH 23390. However, in contrast to dopamine, the actions of d-amphetamine, bicuculline, and veratridine were attenuated or abolished by pharmacological agents (such as 6-OH- dopamine, alpha-methyl-p-tyrosine, or reserpine) known to reduce the release of dopamine from dopaminergic neurons. Moreover, the actions of veratridine and bicuculline were prevented by tetrodotoxin, indicating that one or more neurons in the dopamine pathway are spike-generating. We conclude that d-amphetamine, bicuculline, and veratridine reduce electrical coupling between the axon terminals of the turtle horizontal cells by promoting the release of endogenous dopamine from the dopaminergic amacrine cells previously identified (Witkovsky et al., 1984). Electron-microscopic observations revealed that 6-OH-dopamine selectively attacked this population of amacrine cells. No degenerating terminals were found adjacent to the horizontal cell axon terminals. On this basis, we postulate that dopamine reaches the horizontal cell by diffusion through the extracellular space.